Design of Urban resilience model in emergency situations - Dongxun Jiang; Zhaocheng Li (PLoS ONE, 2026)
In response to the current demand for urban resilience in emergency situations, we have developed an urban resilience assessment system for responding to sudden natural disasters based on housing data, infrastructure data, as well as Gross Domestic Product(GDP) and population data from 25 regions in Changchun and Hohhot. Subsequently, we conducted multidimensional consideration and analysis of the infrastructure service levels of the two cities, and based on this, designed aurora resilience in emergency situations. We have introduced three evaluation indicators: emergency response speed, resource allocation efficiency, and per capita facility density. We use Analytic Hierarchy Process (AHP) to analyze importance weights and obtain robustness of comprehensive infrastructure. Based on this, we used TOPSIS method to analyze the problems faced by two cities at different service levels and provided long-term and short-term investment strategies. Finally, we discussed the advantages and disadvantages of current urban resilience assessment models and conducted consistency and sensitivity analysis on the AHP algorithm. We found that existing models can to some extent reflect the stability and resilience of cities.